The mediating role of organizational intelligence in the relationship between quantum leadership and innovative behavior - Bilgen, Ayşe; Elçi, Meral (Frontiers in Psychology, 2022)
The present study aimed to examine, it was aimed to examine the mediator effect of organizational intelligence between quantum leadership and innovative behavior of employees in health organizations. The data of the study were collected from 626 healthcare professionals working in hospitals and health centers in Istanbul, Turkey, by survey method. After the analysis of normality, validity and reliability, the hypotheses of the research were tested on the LISREL program using the structural equal modelling. The findings showed that the three hypotheses of the research were confirmed: quantum leadership and organizational intelligence affect the innovative behaviors of employees positively and significantly, and organizational intelligence has a mediator effect between quantum leadership and the innovative behavior of employees. It is imperative that healthcare organizations, which are likely to encounter chaos and crisis risks such as the Covid-19 pandemic, follow innovation in order to provide better quality services. Quantum leadership and organizational intelligence are necessities in terms of revealing innovative behavior for healthcare organizations operating in a dynamic and chaotic environment. Since the effects of quantum leadership have not been studied in health organizations, this study makes a contribution to fill this gap. In addition, it is predicted that the findings of this research will be illuminating in terms of innovative behaviors and leadership styles for health organizations that have a vital importance in all societies and have recently experienced an experience such as Covid-19.